Analisis Risiko Rantai Pasok Bahan Baku Pada Usaha Katering Manakan Sehat Menggunakan FMEA - Sahro, Hanifatus (Undana Press, 2025)
The sustainability of healthy food catering businesses largely depends on the availability of fresh, high-quality, and consistent organic raw materials. However, the supply chain of these raw materials often encounters risks such as limited numbers of suppliers, unstable product quality, and delivery delays. This study aims to analyze supply chain risks of raw materials in healthy food catering businesses in Malang City using the Failure Mode and Effect Analysis (FMEA) method. Primary data were collected through interviews with business owners and procurement staff, as well as questionnaires assessing the severity, occurrence, and detection of risks. The findings reveal that the highest-priority risk is the limited availability of organic raw materials (RPN = 315), followed by variations in raw material quality (RPN = 288) and delivery delays (RPN = 210). This study provides practical contributions by recommending the diversification of organic farmer partners, the implementation of quality standards in procurement, and the strengthening of distribution coordination to ensure the sustainability of healthy food catering businesses.